2012
DOI: 10.4236/sm.2012.22023
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Twitter Sentiment toward Midterm Exams

Abstract: Twitter is the most popular microblogging service today, with millions of its uers posting short messages (tweets) everyday. This huge amount of user-generated content contains rich factual and subjective information ideal for computational analysis. Current research findings suggest that Twitter data could be utilized to gain accurate public sentiment on various topics and events. With help of Twitter Stream API, we collected 260,749 tweets on the subject of midterm exams from students on Twitter for two cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Social media has opened an entirely new path for social science research, especially when it comes to the overlap between human relations and technology. In this respect, the value of user-generated content on social media platforms has been wellestablished and acknowledged since their rich and subjective information allows for favorable computational analysis (Hu, 2012). For instance, recent research explored the social dynamics of sporting events based on Facebook comments (Moreau et al, 2021), while another study disclosed the social semiotics of different attractions using Instagram content (Arefieva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Social media has opened an entirely new path for social science research, especially when it comes to the overlap between human relations and technology. In this respect, the value of user-generated content on social media platforms has been wellestablished and acknowledged since their rich and subjective information allows for favorable computational analysis (Hu, 2012). For instance, recent research explored the social dynamics of sporting events based on Facebook comments (Moreau et al, 2021), while another study disclosed the social semiotics of different attractions using Instagram content (Arefieva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the characteristics of tweets, a weight +1 was assgined to a positive word, −1 to a negative word, +5 to a positive emoticon, and −5 to a negative emoticon, since emoticons are key non-verbal sentiment indicators in tweets. An opinion word combined with a negation word, such as "no" or "not", was assgined to its opposite In [8] we showed that our sentiment predictor performed better than other predictors on tweets. The purpose of this study was to gauge the average Twitter sentiment toward Thanksgiving and Christmas holidays.…”
Section: Tweet Lengths By Hourmentioning
confidence: 72%